2016
DOI: 10.3961/jpmph.16.034
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Geographic Units of Analysis on Measuring Geographic Variation in Medical Services Utilization

Abstract: Objectives:We aimed to evaluate the effect of geographic units of analysis on measuring geographic variation in medical services utilization. For this purpose, we compared geographic variations in the rates of eight major procedures in administrative units (districts) and new areal units organized based on the actual health care use of the population in Korea.Methods:To compare geographic variation in geographic units of analysis, we calculated the age–sex standardized rates of eight major procedures (coronary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 18 publications
1
28
0
Order By: Relevance
“…It has been suggested that SCVs greater than 5.4 suggest high variation, and those greater than 10 very high variation [29,30]. As indicated by Mcpherson et al, the SCV was presented as being multiplied by 100 [28,31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that SCVs greater than 5.4 suggest high variation, and those greater than 10 very high variation [29,30]. As indicated by Mcpherson et al, the SCV was presented as being multiplied by 100 [28,31].…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the geographic variations in ACSC hospitalization rates, we assessed the degree of the variation in the ACSC hospitalization rates by comparing it to the variation in the other procedures [31,34]. We found that the CV and SCV in the ACSC hospitalization rates were markedly higher than the other medical procedures, such as percutaneous transluminal coronary angioplasty, surgery after hip fracture, knee-replacement surgery, cesarean section, hysterectomy, computed tomography scan, and magnetic resonance imaging scan.…”
Section: Discussionmentioning
confidence: 99%
“…We examined average healthcare use and costs related LLCs in the last year of life for each patient in terms of the number of hospitalizations, inpatient days, OPD visits, and ED visits. In order to identify the geographic distribution of deaths and any imbalances in healthcare use regarding LLCs between 17 administrative districts, relevance indices (RIs) were calculated by dividing the number of deceased patients with LLCs who used hospitals located in the same geographic region as their residence by the total number of deceased residents with LLCs in that area 18,19 . RI was analysed based on the sum of data from 2013 to 2015, considering the small number of deceased patients with LLCs.…”
Section: Variablesmentioning
confidence: 99%
“…The hospitalization rates for asthma among age groups show a similar trend with the prevalence of asthma: highest among children, which is followed by the elderly. However, the regional difference in the hospitalization rates is far above the difference in the prevalence of asthma in Korea [25], and the variation in the hospitalization rates for asthma is unusually large compared with hospitalization rates of other common causes, which are also considered large compared to other countries [31,41]. This suggests that the decision for hospitalization for asthma in Korea is highly discretionary.…”
Section: Discussionmentioning
confidence: 99%